Investigation of the nanomechanical and tribological properties of dental materials. (9th January 2009) - Al-Haik, Marwan S.; Trinkle, Shane; Garcia, Daniel; Yang, Fan; Martinez, Ulises; Sumali, Hartono; Miltenberger, Scott
This study utilises nanoindentation and nanoscratch for testing the human enamel and dentine and three biocompatible dental filling materials: epoxy nanocomposite, glass ionomer, and silver amalgam. Nanoindentation gave hardness and Young's modulus. Nano-scratch gave critical load in the scratch test, and resistance to sliding wear. The results show that the silver amalgam filling has a higher modulus of elasticity, hardness and wear resistance than the nanocomposite. These relatively nondestructive mechanical characterisation techniques may assist in better understanding the mechanical behaviour of the dental fillers and thus facilitate the design of robust fillers with excellent mechanical properties.